PERAN POS BANTUAN HUKUM DALAM MELAKUKAN PENDAMPINGAN HUKUM KEPADA TERDAKWA SELAMA MASA PANDEMI COVID-19 - Annisa Rahmadiana; Lies Sulistiani; Ajie Ramdan (Fakultas Hukum Univesitas Kristen Indonesia Paulus, 2023)
Abstract Obtaining legal aid is one of the defendant's rights at trial. There have been more or less barriers in providing legal aid to defendants during COVID-19. The shift in the legal aid mechanism during the Covid-19 Pandemic, which used to be carried out face-to-face to online using electronic intermediaries, is considered to have triggered the emergence of obstacles and obstacles for Posbakum to provide optimal legal aid to the defendant. Based on this, this research was conducted to determine the extent of Posbakum's role as a provider of free legal services in court and the effectiveness of the implementation of legal aid provided by Posbakum to defendants during the Covid-19 Pandemic. The research was conducted using empirical legal methods so that the problems were not only seen as normative, but also directly the realities that occurred in the field. Field data was obtained through observations and interviews with several informants who were involved in the process of providing legal aid. The results of the study show that the implementation of the provision of legal aid carried out by the Cibinong Court Posbakum during the Covid-19 Pandemic was not fully effective because in practice there were still obstacles that prevented legal aid from being provided optimally, as a result of limited interaction and communication between advisers law with the accused and the absence of inadequate facilities or infrastructure. Keywords: Legal Aid, Posbakum, Defendant